Building a Website as a Learning Media at SMP Negeri 1 Gunung Tanjung, Tasikmalaya Regency - Masiho Pandiangan (Journal of Intelligent Decision Support System (IDSS), 2021)
Cooperatives are institutions that run on the principle of kinship. Cooperative activities prioritize the welfare of their members and aim to increase the economic growth of the community. In the context of quality control and improvement, it is necessary to assess the health of cooperatives from both external and internal parties of the cooperative itself. So far, the health assessment of cooperatives and savings and loan units is still done manually. This affects decision making when viewed from the speed factor, calculations and the availability of supporting data. The results of this health assessment are the starting point for the community to give trust. With the health predicate rating system for savings and loan cooperatives and web-based savings and loan units, the officers and owners of cooperatives can provide a quick health assessment. The cooperative aspect is based on PerMen NO. 14/PER/M.KUKM/XII/2009 namely Capital, Assets, Management, Earning. Liquidity, Independence and growth and identity. This system generates cooperative health scores and predicates, dashboard information as a visualization of the assessment results, prints certificates and prints assessments